NILAI ETIKA DALAM NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KARYA HAMKA - Ismawirna, Ismawirna; Erfinawati, Erfinawati; Adelia, Ananda (Jurnal Dedikasi Pendidikan, 2025)
The aim of this research is to describe and identify the ethical values contained in the novel Tenggelamnya Kapal Van Der Wijck by Hamka. The method used in this research is descriptive qualitative. The data source is the novel Tenggelamnya Kapal Van Der Wijck by Hamka. The data collection technique uses reading and listening techniques and note-taking techniques. Data were analyzed using qualitative descriptive analysis with informal presentation of the analysis results. The results of this research show that there are several ethical values in the novel Tenggelamnya Kapal Van Der Wijck by Hamka, 5 data were found, the forms of ethical values include: religious values, moral values, social values, and descriptive ethical values and normative ethics. The religious value is that every human being needs gratitude so that human life can be prosperous and happy. Moral values, namely a person's good and bad, can be seen from their polite, friendly, sincere, affectionate and responsible attitudes. The social value in this novel is that humans must respect and respect each other; and helping each other. Normative Ethics describes human behavior as it is. Meanwhile, descriptive ethics is how patterns of human behavior are related to situations and realities that are entrenched in people's lives